Stiffened Thin Shell Domes - Buchert, Kenneth P. (Engineering Journal, 1964)
The design of ever larger clear span roofs is a challenge to structural engineers, architects, fabricators and steel producers. The type of roof proposed in this paper is a thin steel shell that is either reinforced with stiffeners or is made of two thin shells that form a double or "sandwich" shell. It is proposed that this type of roof could be used as an economical solution for covering stadiums, tanks, supermarkets, shopping centers and eventually to cover significant areas of cities. The use of shell type structures has increased significantly in recent years. The trend in shell construction has been toward larger and thinner shells. As shells are made larger and thinner, elastic buckling becomes one of the most important design considerations and construction cost becomes of prime importance. Actually elastic buckling has been a major factor in limiting the size of certain types of shells.